Sample preparation and orthogonal chromatography for broad polarity range plasma metabolomics: Application to human subjects with neurodegenerative dementia - Armirotti, Andrea; Basit, Abdul; Realini, Natalia; Caltagirone, Carlo; Bossù, Paola; Spalletta, Gianfranco; Piomelli, Daniele (Analytical biochemistry, 2014)
We describe a simple protocol for the preparation and orthogonal hydrophobic/hydrophilic LC–MS/MS analysis of mouse and human plasma samples, which enables the untargeted (“shotgun”) or targeted profiling of hydrophilic, amphipathic, and hydrophobic constituents of plasma metabolome. The protocol is rapid, efficient, and reliable, and offers several advantages compared to current procedures. When applied to a training set of human plasma samples, the protocol allowed for the rapid acquisition of full LogP metabolic profiles in plasma samples obtained from cognitively healthy human subjects and age-matched subjects with mild cognitive impairment or Alzheimer’s disease (n=15 each). Targeted analyses confirmed these findings, which are consistent with data previously published by other groups.